2014
DOI: 10.1111/1749-4877.12073
|View full text |Cite
|
Sign up to set email alerts
|

Small mammal community succession on the beach of Dongting Lake, China after the Three Gorges Project

Abstract: Although the Three Gorges Project (TGP) may have affected the population structure and distribution of plant and animal communities, few studies have analyzed the effect of this project on small mammal communities. Therefore, the present paper compares the small mammal communities inhabiting the beaches of Dongting Lake using field investigations spanning a 20-year period, both before and after the TGP was implemented. Snap traps were used throughout the census. The results indicate that the TGP caused major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 65 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…Reliable spatial distribution estimates of population density are crucial to population conservation and habitat management of elusive endangered species (Sollmann et al, 2013;Li and Wang, 2013;Zimmermann et al, 2013;Zhang et al, 2014). Camera trapping is an effective, non-invasive technique for wildlife surveys and is currently a popular tool for estimating population sizes of elusive, rare species (Karanth, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Reliable spatial distribution estimates of population density are crucial to population conservation and habitat management of elusive endangered species (Sollmann et al, 2013;Li and Wang, 2013;Zimmermann et al, 2013;Zhang et al, 2014). Camera trapping is an effective, non-invasive technique for wildlife surveys and is currently a popular tool for estimating population sizes of elusive, rare species (Karanth, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the manipulation of flow regulation by the TGR might also influence the small mammal communities inhabiting the beaches of rivers and lakes in the middle reaches of the Yangtze River, downstream of the TGR. To date, a few small mammal studies have been conducted, with a focus on the small mammals inhabiting the beach areas in the Dongting Lake region and the Poyang Lake region [35,[51][52][53][54][55].…”
Section: Small Mammals In the Downstream Areamentioning
confidence: 99%
“…Historical data for Dongting Lake showed that, before the TGP, extensive flooding in summer made the lake beaches unstable habitats for small mammal populations, other than M. fortis [54], with studies suggesting that the lake beach represented suitable living and breeding habitat for the vole living [56,57]. It was predicted that the regulation of water flow by the TGR might reduce water levels in fall and increase the amount of time that M. fortis had access to its preferred beach habitats, which would, consequently, result in larger vole populations and greater damage to surrounding crops [51,52].…”
Section: Small Mammals In the Beach Of Dongting Lake Areamentioning
confidence: 99%
“…As human populations grow, anthropogenic disturbances are imposing increasing threats to biodiversity and ecosystem functioning (Dirzo et al 2014;Zhang et al 2014). Livestock grazing has been recognized as one of the oldest and most geographically expansive forms of terrestrial anthropogenic activities Pielke et al 2011), and has significantly shaped grassland ecosystems through both direct and indirect effects (Golluscio et al 2009).…”
Section: Introductionmentioning
confidence: 99%